Rhyolitic Ash Promoting Organic Matter Enrichment in a Shallow Carbonate Platform: A Case Study of the Maokou Formation in Eastern Sichuan Basin - Meng, Qingqiang; Pang, Qian; Hu, Guang; Jin, Zhijun; Zhu, Donhya; Liu, Jiayi; Zhang, Chuanwen (Frontiers in Earth Science, 2022)
Volcanic ash improves the amount of nutritive elements in the lake and ocean, but it is not fully understood how volcanic ash influences the total organic matter content (TOC) and bio-precursor, and the scope. A volcanic layer, measuring 5cm in thickness, was examined using electron microscopy scanning, TOC/TS, rock pyrolytic, and inorganic geochemical analyses. The study shows that the TOC content in the overlying shales increases by 18 wt.% on average, and the vertical scope of influence on shales is twice as thick as the volcanic layer. Organic matter enrichment is attributed to the fact that the volcanic layer provides nutritive elements and meanwhile changes the oxidation-reduction condition. Large variations of hydrogen index (HI) and oxygen index (OI) in the lower and upper parts of the volcanic layer is related to terrestrial organic matter vanishing, due to volcanic eruption and subsequently more terrigenous organic matter migrating into the ocean. Little change of the bio-precursor in the overlying and underlying shales may be related to the fast restoration within the ocean and land ecosystems after a volcanic eruption. The decrease in terrigenous sediments indicated by Rb/Sr, Zr/Y, and ∑REE after a volcanic eruption indirectly reflects fast restoration of terrestrial vegetation boom. This study could decipher the influence of volcanic ash on the qualities of the source rock, which can provide a better understanding on discovering more economically petroleum reservoirs in igneous rocks.